A REPÚBLICA E RUI BARBOSA: O PROJETO DE INDUSTRIALIZAÇÃO EM UM PAÍS DE BASES AGRÍCOLAS (1889-1891) - Santos, Vinícius Silva dos (2021)
The present dissertation research aims to analyze Rui Barbosa´s economic thought and performance as the first minister of Finance of the republican period, a position he held between the period from November 15, 1889 to January 20, 1891, in order to to id